Μαθηματική προσομοίωση της πλημμύρας στη Μάνδρα με χρήση μοντέλου TELEMAC - Μαρκόπουλος-Σαρίκας, Γεώργιος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών. Τομέας Υδατικών Πόρων και Περιβάλλοντος, 2018)
The incident of a flash flood in Mandra, Attica on 15th of November 2017 resulted in 23 people’s death and another 24 human injuries. Almost all the town area was affected, since numerous properties flooded or, even worse, got totally destroyed. Also, a great impact was observed at Mandra industrial area and adjacent settlements, while large avenues to the South of Mandra (Attiki Odos, Ionia Odos, Old National Road Elefsina- Theba) remained closed and unapproachable for a few hours. Scope of the present work was the preliminary formulation of a numerical model for the simulation of the hydro-dynamic behavior of the aforementioned incident, employing the open source code TELEMAC-2D software for the wider area of Mandra. The model was implemented on a region, large enough to comprise all the affected areas, and also upstream until the terminal junction of an adjacent watercourse with the two major streams affecting Mandra, Soures stream and Agia Aikaterini stream. The model formulation was based on the digital elevation model (DEM), provided by National Cadastre and Mapping Agency SA and on the use of Corine 2012 land usage maps. Employing GIS software (ArcGIS) and mathematics software (MatLab), provided by N.T.U.A. common facilities, all data were processed and the unstructured triangular irregular mesh of the surface geometry and bottom friction was produced. After a few trials the final formation of the mesh was determined in order to achieve both satisfactory precision and analysis swiftness. The usage of input hydrograph, proposed by G. Tsakiris, Professor in SORSE, N.T.U.A. during TCG informing affair, was chosen to accomplish the simulation of the inundation. That hydrograph was deemed adequate and requisite for the initial formulation of the model. Data were collected from other relevant researches concerning that incident and additionally after in situ autopsy and interviews so as to verify the reliability of the simulation model. Significant help also came from residents that had recorded the evolution of the incident and were eager to contribute to this work. Utilizing as benchmarks the points where information about depths and time of flow existed and points with known flow depth the evaluation of the model was accomplished. During this evaluation the conclusions emerging from the simulation were registered and simultaneously proposals were expressed for the improvement of the model, aiming to further investigation of factors that affect the final result.